Netralitas Birokrasi (ASN, Kepala Desa Beserta Perangkat Desa) Di Kecamatan Botupingge Dan Kecamatan Suwawa Selatan - Mahmud, Ramli; Djaafar, Lucyane; M. Wantu, Sastro; Adjie, Zulfikar (Journal Of Human And Education (JAHE), 2024)
Bureaucratic neutrality has always been a significant challenge in every democratic event, whether in general elections (Pemilu) or local elections (Pemilukada). In the upcoming 2024 simultaneous elections, various strategies have been formulated by election organizing bodies (KPU and Bawaslu) at both the central and regional levels to strengthen and raise awareness among bureaucrats to maintain neutrality in the electoral process. However, these efforts have yet to yield optimal results, as bureaucracies are frequently utilized as tools to mobilize support for vote acquisition. Factors such as familial ties, career motives of campaign teams, superiors, candidate pairs, and the position of regional heads as personnel authorities (PPK) make it difficult for civil servants (ASN) to remain neutral. Based on this context, this community service aims to: 1) Identify the vulnerabilities of election violations by bureaucrats (civil servants, village heads, and village apparatus); 2) Build awareness within the bureaucracy to refrain from engaging in practical politics; and 3) Provide political education to strengthen bureaucratic political preferences, encouraging them to become intelligent voters who prioritize independence and neutrality in the lead-up to the 2024 simultaneous elections in Bone Bolango Regency.